Fostering communicative competence: a task-based approach to public speaking materials development - Ariatna; Nuran, Ade Aini; Nasution, Nazlah Syahaf (UNIB Press, 2025)
While ample studies have explored the creation of task-based materials to enhance the English proficiency of university students, there has been limited research on how such materials can be tailored to promote university students' public speaking competence. This paper presents findings from a research and development (R&D) study aimed at refining English teaching materials using a task-based approach to bolster university students' public speaking abilities. The study was conducted in the English Language Department at a public university in Medan and followed the R&D model by employing a multi-phase methodology. Initially, a needs analysis was carried out using a questionnaire to gather student data, focusing on their learning needs and preferences for public speaking skill development. The data were analysed using descriptive statistics to identify key trends. Based on the findings, task-based public speaking materials were developed, featuring structured debates, role-plays, and presentations that encouraged students to engage in real-world speaking tasks. These materials aimed to cultivate both linguistic and strategic competencies necessary for effective public speaking in academic and professional contexts. The materials were then validated through expert evaluation to ensure content accuracy, alignment with public speaking objectives, and pedagogical relevance. Following validation, the materials were piloted in the classroom, and qualitative feedback was collected from both the lecturer and students through interviews and surveys. The validation process confirmed the practicality and effectiveness of the task-based materials. Additionally, both the lecturer and students reported positive outcomes, noting significant improvements in the students' public speaking competence and increased engagement due to the real-world relevance of the tasks.